Diagnostic and public health investigation of Mycobacterium tuberculosis infection in a dog in Ontario, Canada. (March 2022) - Haydock, Luke A. J.; Abrams-Ogg, Anthony C. G.; Weese, J. Scott; Goldstein, Michael R.; Clifford, Amy B.; Sebastian, Adrian; Rea, Elizabeth H.; Jamieson, Frances B.; Duncan, Carla; Andrievskaia, Olga; Savic, Mirjana; Slavic, Durda; et al.
A 4-y-old, female mixed-breed dog was presented to the Ontario Veterinary College for further evaluation of multiple pulmonary and hepatic masses, intrathoracic lymphadenitis, and recent development of a pyogranulomatous pleural effusion. Along with other comprehensive tests, a thoracic lymph node biopsy was performed, and Mycobacterium tuberculosis complex infection was confirmed by real-time PCR. The dog's condition declined post-operatively, and euthanasia was elected. Postmortem examination confirmed severe granulomatous pneumonia, hepatitis, intrathoracic and intraabdominal lymphadenitis, omentitis, and nephritis. Line-probe assays performed on samples collected postmortem confirmed the species as M. tuberculosis . 24-loci MIRU-VNTR genotyping, spoligotyping, and whole-genome sequencing revealed relations to known human isolates, but no epidemiologic link to these cases was investigated. Given the concern for potential human exposure during this animal's disease course, a public health investigation was initiated; 45 individuals were tested for M. tuberculosis exposure, and no subsequent human infections related to this animal were identified. Our case highlights the need for more readily available, minimally invasive testing for the diagnosis of canine mycobacteriosis, and highlights the ability of canid species to act as potential contributors to the epidemiology of M. tuberculosis infections.